Scleral Abscess of the Infusion Port Site Following Pars Plana Vitrectomy and its Management - Mansoori, Tarannum; Srirampur, Arjun; Agraharam, Satish Gooty (Nepalese Journal of Ophthalmology, 2022)
Introduction: Mycotic scleral abscess after pars plana vitrectomy (PPV) is a rare entity and a scleral abscess caused by Aspergillus flavus following PPV has not been reported in the literature. We describe the clinical presentation, complication and management outcome in a patient, who developed a mycotic scleral abscess at the infusion port site after 20 gauge pars plana vitrectomy. Case: Two weeks after pars plana vitrectomy, a patient presented with a scleral abscess at the site of infusion port. He was a known diabetic, had a history of pulmonary tuberculosis and was using steroid eye drop at the time of presentation. Surgical debridement of the abscess was performed and he was treated with topical and systemic antifungal drugs. After three days of incubation, Sabouraud dextrose agar identified growth of Aspergillus flavus. After showing initial resolution, at 4 weeks follow up, the scleral abscess was noted to have progressed to involve the adjacent cornea. Corneoscleral patch graft was performed and treatment with topical and systemic antifungal was continued, which led to complete resolution of the corneoscleral abscess with corneal opacity and scar formation, over a period of eight weeks.  Conclusion:  Scleral abscess is a rare complication after pars plana vitrectomy and requires early and appropriate treatment to decrease the ocular morbidity. Dissemination of the infection to involve the cornea can be managed with corneo scleral patch graft and appropriate antifungal medications to salvage the eye.